The treatment of diffuse large B-cell non-Hodgkin’s lymphoma in pregnancy: a case report and a review of literature - Stepanovic, Boban; Tausanovic, Katarina; Zivaljevic, Vladan; Kesic, Vesna (Medical Research, 2023)
Objective: Hodgkin’s lymphoma (HL) is the most common type of lymphoma diagnosed during pregnancy while the occurrence of non-Hodgkin’s lymphoma (NHL) is rare because the peak incidence of disease occurs after childbearing age. Case report: We present a case of 36-year-old woman, in the 13th week of pregnancy, admitted to our department for suspected thyroid lymphoma. She presented with neck swelling, respiratory distress, and dysphagia. After biopsy, histopathological analysis led to the diagnosis of primary diffuse large B-cell mediastinal NHL. The recommendation of multidisciplinary medical team was to start the treatment immediately with R-CHOP for a total of 6-8 cycles. Five years have passed since the beginning of treatment, the disease is still in remission and the child is at normal level of growth for his age. Conclusion: Lymphomas in pregnancy represent the challenge for the medical team as well for the patient. With early diagnosis and appropriate therapy, despite all the risks, it is possible to bring mother into remission without endangering the offspring.